Optimization of biodiesel production by microwave irradiation-assisted transesterification for waste cooking oil-Calophyllum inophyllum oil via response surface methodology - Milano J.; Ong H.C.; Masjuki H.H.; Silitonga A.S.; Chen W.-H.; Kusumo F.; Dharma S.; Sebayang A.H. (Elsevier Ltd, 2023)
Alternative fuels; Catalysts; Energy efficiency; Energy utilization; Fatty acids; Irradiation; Methanol; Microwave irradiation; Oils and fats; Physicochemical properties; Regression analysis; Surface properties; Synthetic fuels; Transesterification; Biodiesel production; Box-Behnken design; Box-Behnken experimental design; Catalyst concentration; Fatty acid methyl ester; Non-edible oil; Response surface methodology; Transesterification process; Biodiesel